2007
DOI: 10.1017/s0031182007002314
|View full text |Cite
|
Sign up to set email alerts
|

Re-feeding rapidly restores protection againstHeligmosomoides bakeri(Nematoda) in protein-deficient mice

Abstract: This study determined whether the timing of re-feeding of protein-deficient mice restored functional protection against the gastrointestinal nematode, Heligmosomoides bakeri. Balb/c mice were fed a 3% protein-deficient (PD) diet and then transferred to 24% protein-sufficient (PS) diet either on the day of primary infection, 10 days after the primary infection, on the day of challenge infection, or 7 days after the challenge infection. Control mice were fed either the PD or PS diet. Onset of challenge, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…The lack of parasite-induced anorexia across the infected mice was unexpected because such a reduction had been observed in previous studies with this mouse-parasite model (Houdijk and Bünger, 2006;Coltherd et al 2009) and in other studies using H. bakeri (Boulay et al 1998;Ing et al 2000;Tu et al 2007). A reduction in feed intake would be expected to occur mainly during the initial stages of infection (Coltherd et al 2009;Kyriazakis, 2010), and it might be that this would only have been evident above a certain level of infection pressure (Sandberg et al 2006).…”
Section: Body Weight Food Intake and Fat Percentagementioning
confidence: 56%
“…The lack of parasite-induced anorexia across the infected mice was unexpected because such a reduction had been observed in previous studies with this mouse-parasite model (Houdijk and Bünger, 2006;Coltherd et al 2009) and in other studies using H. bakeri (Boulay et al 1998;Ing et al 2000;Tu et al 2007). A reduction in feed intake would be expected to occur mainly during the initial stages of infection (Coltherd et al 2009;Kyriazakis, 2010), and it might be that this would only have been evident above a certain level of infection pressure (Sandberg et al 2006).…”
Section: Body Weight Food Intake and Fat Percentagementioning
confidence: 56%
“…Body condition is an important aspect of health that can influence an animal's ability to fight off infection, and nutrition may have an impact on body condition. Constant feeding of mice with nematode infections, while prolonging nematode survival, has been shown to increase weight gain and allowed for parasite clearance in the host (Tu et al 2007). A balanced diet provided to schoolchildren in Burkina Faso, Africa has also been shown to decrease the prevalence of intestinal helminths such as hookworms, roundworms, and tapeworms (Sanou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral concentrations in the liver in infected mice were analyzed by one-way ANOVA, with average daily food intake as the covariate. Analysis of covariance was used, because food intake directly affects mineral intakes, and previous studies have shown that both protein deficiency and infection can influence food intake in our model [12,13]. Overall, mineral distributions in the spleen, serum, and liver were modified independently by protein deficiency and H. bakeri infection.…”
Section: Discussionmentioning
confidence: 99%
“…Diet composition was based on National Research Council mouse requirements [23], and egg-white-based semi-purified powdered diets were formulated as previously described [12]. A 3% protein diet was fed as the PD diet.…”
Section: Mice and Dietsmentioning
confidence: 99%
See 1 more Smart Citation